Faktor-Faktor Yang Mempengaruhi Ketepatan Waktu Penyampaian Laporan Keuangan Pada Perusahaan Perdagangan, Jasa & Investasi - Ratna Dewi; Ni Nyoman Yuliati; Sofiati Wardah (Akuntabel: Jurnal Ilmiah Akuntansi, 2024)
This research aims to determine the influence of Profitability, Company Size, Debt To Equity Ratio, Auditor Quality, and Company Age on the Timeliness of Financial Report Submission. The population of this study comprises 29 companies in the trade, services, and investment sector, specifically in the sub-sector of large-scale production trade, listed on the Indonesia Stock Exchange from 2019 to 2022. The sample was selected using purposive sampling. The total sample taken is 14 companies. The data analysis technique used is logistic regression. The test results indicate that Profitability, Company Size, Debt to Equity Ratio, Auditor Quality, and Company Age do not affect the timeliness of financial report submission.